2016
DOI: 10.1016/j.celrep.2016.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Lipid Droplet Proteome Analysis Identifies Annexin A3 as a Cofactor for HCV Particle Production

Abstract: Lipid droplets are vital to hepatitis C virus (HCV) infection as the putative sites of virion assembly, but morphogenesis and egress of virions remain ill defined. We performed quantitative lipid droplet proteome analysis of HCV-infected cells to identify co-factors of that process. Our results demonstrate that HCV disconnects lipid droplets from their metabolic function. Annexin A3 (ANXA3), a protein enriched in lipid droplet fractions, strongly impacted HCV replication and was characterized further: ANXA3 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 48 publications
(58 reference statements)
5
61
0
Order By: Relevance
“…The HCV reporter Jc1 p7-GLuc-2A-NS2 was cloned as described 34 , but with a modified F2A site. For shRNA constructs, the primers listed below were cloned into a modified pSicoR-MS1-Puro vector 61 using the following target sequences: IRF3, GGAGGCAGTACTTCTGATA; RIG-I, GAAACTTGCCAGTTATATA, STAT1, GGTGGTATTTAGTCTATTA; STAT2, GAACAGTCCTGTTCAGAAA; TLR3, GGAGATTCCAGATTATAAA, and NT-control, GTCAAGTCTCACTTGCGTC described in 62 . Complete primer sequences are available on request.…”
Section: Methodsmentioning
confidence: 99%
“…The HCV reporter Jc1 p7-GLuc-2A-NS2 was cloned as described 34 , but with a modified F2A site. For shRNA constructs, the primers listed below were cloned into a modified pSicoR-MS1-Puro vector 61 using the following target sequences: IRF3, GGAGGCAGTACTTCTGATA; RIG-I, GAAACTTGCCAGTTATATA, STAT1, GGTGGTATTTAGTCTATTA; STAT2, GAACAGTCCTGTTCAGAAA; TLR3, GGAGATTCCAGATTATAAA, and NT-control, GTCAAGTCTCACTTGCGTC described in 62 . Complete primer sequences are available on request.…”
Section: Methodsmentioning
confidence: 99%
“…They showed dramatic changes in lipid droplet protein association. In particular, HCV infection causes recruitment of annexin A3 to these organelles and this relocalization is necessary for a virus particle maturation step after capsid envelopment (172) (Fig. 3D).…”
Section: Molecular and Cellular Proteomics 16 Supplement 4 S83mentioning
confidence: 99%
“…LD-associated proteins are key to their diverse functions. On top of a core set of a few dozen of LD-associated proteins (e.g., reviewed in Hodges and Wu, 2010), proteomic studies with LDs isolated from diverse cell lines, tissues, and organisms revealed the presence of likely hundreds of additional proteins (Beller et al, 2006;Cermelli et al, 2006;Ding et al, 2012;Fei et al, 2011;Li et al, 2016;Rö sch et al, 2016;Schmidt et al, 2013;Vrablik et al, 2015;Zhang et al, 2011). While the role of selected LD-associated proteins, such as the perilipins, in energy metabolism regulation is well investigated (e.g., reviewed in Kimmel and Sztalryd, 2016), many proteins still lack a detailed analysis.…”
Section: Introductionmentioning
confidence: 99%